PEMBERDAYAAN PEMBUDIDAYA IKAN MELALUI TRANSFER TEKNOLOGI PAKAN BERBASIS LEAST COST FORMULATION (LCF) DENGAN FEED SUPPLEMENT DI KABUPATEN NAGAN RAYA - Samuki, Khairul; Hasibuan, M. Barru Airil Fizra; Suhendra, Rivansyah; Saputra, Fazril; Asra, Saiful; Abdan, Mu'amar; Diansyah, Sufal (Universitas Mataram, 2025)
This community service activity was driven by the high dependence of fish farmers on commercial feed, which results in high production costs and low business efficiency. One of the partner groups, UPR Clarias Fish Farm in Nagan Raya Regency, experienced difficulties in accessing independent feed formulation technology. The goal of this activity is to transfer feed technology based on Least Cost Formulation (LCF), enriched with feed supplements, to improve efficiency and self-sufficiency in feed production. Implementation methods include socialization, workshops, technical assistance, and regular monitoring and evaluation. The results of the activity showed a significant increase in participants’ understanding of feed formulation, as seen from the average pretest score of 45.3, which rose to 82.3 in the posttest. Most partners have begun to produce their feed independently and have reported a decrease in operational costs. The evaluation also recorded an increase in partners’ confidence in managing technology-based aquaculture businesses. Thus, this program has not only successfully improved the technical capacities of fish farmers but has also had a direct impact on production efficiency and the competitiveness of local fisheries businesses.